Acetabular blood flow during total hip arthroplasty - ElMaraghy, Amr W. (Canadian Medical Association, 2000)
OBJECTIVE: To determine the immediate effect of reaming and insertion of the acetabular component with and without cement on periacetabular blood flow during primary total hip arthroplasty (THA). DESIGN: A clinical experimental study. SETTING: A tertiary referral and teaching hospital in Toronto. PATIENTS: Sixteen patients (9 men, 7 women) ranging in age from 30 to 78 years and suffering from arthritis. INTERVENTION: Elective primary THA with a cemented (8 patients) and noncemented (8 patients) acetabular component. All procedures were done by a single surgeon who used a posterior approach. MAIN OUTCOME MEASURE: Acetabular bone blood-flow measurements made with a laser Doppler flowmeter before reaming, after reaming and after insertion of the acetabular prosthesis. RESULTS: Acetabular blood flow after prosthesis insertion was decreased by 52% in the noncemented group (p < 0.001) and 59% in the cemented group (p < 0.001) compared with baseline (prereaming) values. CONCLUSION: The significance of these changes in periacetabular bone blood flow during THA may relate to the extent of bony ingrowth, periprosthetic remodelling and ultimately the incidence of implant failure because of aseptic loosening.